2013
DOI: 10.1038/aps.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides suppress ICAM-1 and VCAM-1 expression in TNF-α-treated human vascular endothelial cells by blocking NF-κB activation

Abstract: Aim: To investigate the effects of Astragalus polysaccharides (APS) on tumor necrosis factor (TNF)-α-induced inflammatory reactions in human umbilical vein endothelial cells (HUVECs) and to elucidate the underlying mechanisms. Methods: HUVECs were treated with TNF-α for 24 h. The amounts of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) were determined with Western blotting. HUVEC viability and apoptosis were detected using cell viability assay and Hoechst staining, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Several lines of evidence have demonstrated that ROS contribute to ICAM-1 expression induced by different stimuli in various cell types (8,34). In addition, NADPH oxidase is an important enzymatic source for the production of ROS under various pathologic conditions.…”
Section: Involvement Of Nadph Oxidase and Ros Generation In Lps-inducmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that ROS contribute to ICAM-1 expression induced by different stimuli in various cell types (8,34). In addition, NADPH oxidase is an important enzymatic source for the production of ROS under various pathologic conditions.…”
Section: Involvement Of Nadph Oxidase and Ros Generation In Lps-inducmentioning
confidence: 99%
“…Accumulated evidence demonstrates that monocyte infiltration plays a crucial role in the pathophysiology of coronary artery diseases including atherosclerosis, which can not only initiate and propagate the accumulation of monocyte-derived macrophages but also produce inflammatory mediators that destabilize atherosclerotic plaques (Kartikasari et al, 2009;Zhu et al, 2013). The monocyte-endothelium cells interactions consist of consecutive processes of monocytes adhesion 3 / 29 and infiltration through the endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Lauric acid has been shown to reduce the expression of transcription factor, NF-kB [21] . NF-kB is a pro-inflammatory transcription factor that activates immune and inflammatory response by controlling the genes expression of a wide spectrum of inflammatory cytokines and cell adhesion molecules [22][23][24] . Hence, the reduction of IFN-g induced VCAM-1 and ICAM-1 expression might be caused by the diminished cellular NF-kB concentration after the treatment of lauric acid.…”
Section: Discussionmentioning
confidence: 99%